Screening of rickettsia sp. In ticks (acari: Ixodidae) collected from small mammals in three recreational forests in Selangor, Malaysia - Ishak, Siti Nabilah; Lim, Fang Shiang; Khoo, Jing Jing; Mohd-Taib, Farah Shafawati (Universiti Kebangsaan Malaysia Press, 2019)
Rickettsia is a gram-negative, non-motile, and obligate intracellular bacterium that usually associated with arthropods vectors such as ticks, fleas, lice and mites. These bacteria have the ability to cause diseases in humans, however, in Malaysia, knowledge on the prevalence and distribution of these bacteria mainly focused on humans and information of these bacteria in small mammal hosts is limited. Thus, this study aims to investigate the presence of Rickettsia sp. in the DNA of tick’s samples collected from small mammals in three different recreational forests in Selangor, Malaysia. Sampling was conducted in which 200 cage traps were set up randomly along streams and forest trails for five nights. A total of 106 fully engorged and adult ticks were collected from 23 individuals of seven small mammals host species. All samples were tested for Rickettsia bacteria based on polymerase chain reaction (PCR) using partial 17-kDa antigen gene. The PCR results obtained from this study showed no infestation of Rickettsia sp. in all tick samples. Our findings revealed that none of the tick samples from these forests’ sites were infected with Rickettsia pathogen, however, more intense and extensive surveillance for Rickettsia sp. from other tick species is still necessary for greater geographical areas across Malaysia. © 2019, Universiti Kebangsaan Malaysia Press. All rights reserved.